Project-Based Learning in mathematics education: A bibliometric study on 2014–2023 scopus database - Susanti, Mathilda; Retnawati, Heri; Sulistyaningsih, Eny; Kartianom, Kartianom; Rosyada, Munaya Nikma; Kassymova, Gulzhaina K; Sotlikova, Rimajon (Jurnal Riset Pendidikan Matematika, 2023)
Project-based learning is ommited by the curricula of various countries. For the future development, the extent of research related to project-based learning needs to be mapped. This literature review research does a bibliometric analysis of project-based learning research published in Scopus-indexed journals over the last ten years. There are 802 articles from the Scopus database in 2014-2023. The R package and VOSViewer tools are used to perform bibliometric analysis. The results are analyzed and intepreted, including the distribution per year, subject area, affiliation, country or region, citations, main information, treemap, authorship, most cited documents, relationships between years, dendrogram, collaboration between authors, collaboration between countries and continents, as well as the relationship between keywords in the article. The number of research increased significantly from 2014 to 2022. More than 50% of these came from social sciences field. Universitas Negeri Malang has published the most articles, while the United States is most publications country. Although the United States has the most documents, Spain is the the most cited country. The most cited document is written by Kokotsaki et al. in 2016. United States, China, Australia, France, and the United Kingdom often collaborate between countries and continents.